Cover Picture: Hierarchical Assembly of Monodisperse Hydroxyapatite Nanowires and Construction of High‐Strength Fire‐Resistant Inorganic Paper with High‐Temperature Flexibility (ChemNanoMat 4/2017). Issue 4 (24th March 2017) - Li, Heng; Zhu, Ying‐Jie; Jiang, Ying‐Ying; Yu, Ya‐Dong; Chen, Feng; Dong, Li‐Ying; Wu, Jin
Abstract : High‐strength, flexible, fire‐resistant inorganic paper is greatly needed for many high‐temperature applications. This work demonstrates a new strategy for the fabrication of fire‐resistant hydroxyapatite (HAP) nanowire paper with high flexibility and good mechanical properties. The reported method is simple, low‐cost, environmentally friendly, uses water as the only solvent, and can be scaled up for the large‐scale production of HAP nanowires. The A4‐sized HAP nanowire‐based inorganic paper can be directly printed using a commercial printer. The fire‐resistant HAP nanowire paper can also preserve well its high flexibility even at high temperatures. More information can be found in the Full Paper by Y.‐J. Zhu, J. Wu et al. onpage 259 in Issue 4, 2017 (DOI:10.1002/cnma.201700027 ).